A function f ( x ) is differentiable over all reals, and satisfies f ′ ( x 2 + x + 1 ) = π f ( 1 ) sin π x + f ( 3 ) x + 5 x 2 . Find f ( 7 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great solution!
Just a small detail, in the last step it's positive 5 instead of − 5 . The total is still 9 3 , it's just a typo. :)
Given that:
f ′ ( x 2 + x + 1 ) f ′ ( 1 ) f ′ ( 1 ) ⟹ − f ( 3 ) + 5 f ( 3 ) = π f ( 1 ) sin π x + f ( 3 ) x + 5 x 2 = 0 = 0 − f ( 3 ) + 5 = 0 = 5 Putting x = 0 Putting x = − 1
f ′ ( x 2 + x + 1 ) ∫ f ′ ( u ) d u = π f ( 1 ) sin π x + 5 x + 5 x 2 = ∫ ( π f ( 1 ) sin π x + 5 x + 5 x 2 ) ( 2 x + 1 ) d x = ∫ π f ( 1 ) ( 2 x + 1 ) sin π x + 1 0 x 3 + 1 5 x 2 + 5 x d x Let u = x 2 + x + 1 ⟹ d u = ( 2 x + 1 ) d x Integrate both sides w,r,t, u
Then the equation becomes:
∫ 1 3 f ′ ( u ) d u f ( 3 ) − f ( 1 ) ⟹ 5 f ( 1 ) f ( 1 ) = ∫ 0 1 π f ( 1 ) ( 2 x + 1 ) sin π x + 1 0 x 3 + 1 5 x 2 + 5 x d x = − f ( 1 ) ( 2 x + 1 ) cos π x + ∫ 2 f ( 1 ) cos π x d x + 2 5 x 4 + 5 x 3 + 2 5 x 2 ∣ ∣ ∣ ∣ 0 1 = 4 f ( 1 ) + π 2 f ( 1 ) sin π x ∣ ∣ ∣ ∣ 0 1 + 2 5 + 5 + 2 5 = 4 f ( 1 ) + 1 0 = f ( 3 ) − 1 0 = − 5 = − 1 Integration by parts
Similarly,
f ( 7 ) − f ( 1 ) f ( 7 ) + 1 ⟹ f ( 7 ) = ( 2 x + 1 ) cos π x − π 2 sin π x + 2 5 x 4 + 5 x 3 + 2 5 x 2 ∣ ∣ ∣ ∣ 0 2 = 4 − 0 + 4 0 + 4 0 + 1 0 = 9 3
Problem Loading...
Note Loading...
Set Loading...
( 2 x + 1 ) f ′ ( x 2 + x + 1 ) = f ( 1 ) × ( 2 x + 1 ) π sin π x + f ( 3 ) x ( 2 x + 1 ) + 5 x 2 ( 2 x + 1 )
Integrate both sides,
f ( x 2 + x + 1 ) = { − ( 2 x + 1 ) cos π x + π 2 sin π x } f ( 1 ) + ( 3 2 x 3 + 2 1 x 2 ) f ( 3 ) + 2 5 x 4 + 3 5 x 3 + C .
Substitute x = 0 and x = − 1 , (since then x 2 + x + 1 = 1 )
x = 0 : x = − 1 : f ( 1 ) = − f ( 1 ) + C , 2 f ( 1 ) = C . f ( 1 ) = − f ( 1 ) − 6 1 f ( 3 ) + 6 5 + C , 2 f ( 1 ) = − 6 1 f ( 3 ) + 6 5 + C .
It is immediate that f ( 3 ) = 5 . Substitute x = 1 ,
x = 1 : f ( 3 ) = 3 f ( 1 ) − 3 1 0 f ( 3 ) + 3 8 0 + C , 3 f ( 1 ) = − C − 5 .
Solve the two boxed equations, and you get f ( 1 ) = − 1 , C = − 2 . Hence,
f ( x 2 + x + 1 ) = ( 2 x + 1 ) cos π x − π 2 sin π x + 2 5 x 4 + 5 x 3 + 2 5 x 2 − 2 .
Substitute x = 2 ,
x = 2 : f ( 7 ) = 5 + 4 0 + 4 0 + 1 0 − 2 = 9 3 .